2009
DOI: 10.4314/wajae.v9i1.45666
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal mining of gold with mercury in Ghana

Abstract: The paper examines the environmental impact of artisanal mining of gold with mercury (Hg) in Ghana. In spite of its positive socioeconomic contributions, it is well known that artisanal mining of gold contributes in no small measure to land degradation, loss of biodiversity and natural resources, deforestation, water pollution, etc. In Ghana, these environmental problems remain poorly studied. In the case of Hg pollution, caused by gold extraction using the amalgamation process, total Hg levels in different en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
3
20
1
2
Order By: Relevance
“…Mercury concentrations however marginally declined during this period, such that the least concentration was measured in the upper layers of the sediment core. This finding is consistent with recent decline in sediment Hg levels in Lake Bosomtwe in Ghana (Poste et al 2012), but quite at variance with reported illicit application of Hg by illegal small-scale miners (Donkor et al 2006b;Hilson et al 2007). Two main factors may have contributed to the decreasing trend in Hg concentration.…”
Section: Depth Profile Of Heavy Metals In Sediment Coresupporting
confidence: 73%
“…Mercury concentrations however marginally declined during this period, such that the least concentration was measured in the upper layers of the sediment core. This finding is consistent with recent decline in sediment Hg levels in Lake Bosomtwe in Ghana (Poste et al 2012), but quite at variance with reported illicit application of Hg by illegal small-scale miners (Donkor et al 2006b;Hilson et al 2007). Two main factors may have contributed to the decreasing trend in Hg concentration.…”
Section: Depth Profile Of Heavy Metals In Sediment Coresupporting
confidence: 73%
“…There is a large-scale open-pit and underground gold mine at Obuasi near the River Jimi (which a tributary of the river Ofin upstream of the study area), but mining the rivers and river banks is usually carried out by artisanal (small-scale) miners. The artisanal sector was effectively legalized in 1989 and now represents approximately 10 % of Ghanaian gold production (Donkor et al 2006). The sector works mostly alluvial gold deposits in flood plains, along river banks, and by river dredging.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent use of Hg by artisanal gold miners to extract the gold from the ore (Donkor et al, 2006), the occurrence of As as an impurity in gold ore (Eisler, 2004) and Cu's association with gold mining waste (Ferreira Da Silva et al, 2004) might have led to the high contamination of the elements in the sediments. Table 5 indicates the concentrations of Cd, Pb, Fe, Zn, Mn, Cu, and Hg and As in water samples of the four artisanal mining localities.…”
Section: Resultsmentioning
confidence: 99%